2020
DOI: 10.1007/s00436-020-06797-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Theileria species and Babesia caballi from horses in Nigeria

Abstract: Equine piroplasmosis (EP) is an infectious, tick-borne disease caused by the hemoprotozoan parasites, Theileria equi, Babesia caballi, and a recently reported new species, T. haneyi. Infections by these apicomplexan parasites limit performance and cause economic losses for the horse industry. Equine piroplasmosis is widespread in the northern regions of Nigeria, where an increasing portion of the animal population is composed of horses. This disease has remained epidemiologically challenging, especially as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
0
17
1
Order By: Relevance
“…However, it has been identified in South Africa, Nigeria, The Gambia, and in horses along the US-Mexico border [ 14 , 16 , 17 , 18 ]. Prevalence surveys in The Gambia, Nigeria, and South Africa have also reported co-infection of horses with T. equi and T. haneyi or triple infection with T. equi , T. haneyi , and B. caballi [ 16 , 17 , 18 ]. Both of these Theileria species cause persistent, asymptomatic infection, and both are capable of superinfection in the presence of humoral immunity to the other [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been identified in South Africa, Nigeria, The Gambia, and in horses along the US-Mexico border [ 14 , 16 , 17 , 18 ]. Prevalence surveys in The Gambia, Nigeria, and South Africa have also reported co-infection of horses with T. equi and T. haneyi or triple infection with T. equi , T. haneyi , and B. caballi [ 16 , 17 , 18 ]. Both of these Theileria species cause persistent, asymptomatic infection, and both are capable of superinfection in the presence of humoral immunity to the other [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a Theileria species 18S rDNA variant was elevated as a distinct species [2]. Recent investigations using phylogenetic analysis of rDNA showed Theileria piroplasm variants from horses in Nigeria, including T. haneyi [21,41].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a need for combined high sensitivity molecular and serological studies that enhance the detection of animals exposed to the parasites that cause EP in Nigeria. Only in the last year has the use of molecular tools been reported in Nigeria [ 4 , 21 , 22 ]. Here, we report using the World Organization for Animal Health (OIE) approved cELISA serological tests [ 23 ] combined with molecular detection for T. equi , T. haneyi , and B. caballi to increase our ability to detect horses exposed to pathogens that cause EP.…”
Section: Introductionmentioning
confidence: 99%
“…Infection with T. equi and B. caballi can cause severe economic losses in the equine industry due to the cost of treatment, especially for acutely infected horses, which, in the absence of appropriate treatment, can die [2]. It was found that T. haneyi rarely causes clinical signs in field horses [9], even in splenectomized horses experimentally infected with T. haneyi using the intravenous (IV) route [5,10]. Horses infected with T. equi remain persistently infected, while those affected by B. caballi are infected for an extended period [11].…”
Section: Introductionmentioning
confidence: 99%